(untitled) (Research, Society and Development, 2023)
The incidence of prostate cancer (PCa) has increased worldwide and nationally. The scenario of the growing number of cases has resulted in an expansion of the means of early diagnosis used to detect the pathology. Early detection is responsible for reducing the death rates caused by the disease. The gold standard treatment for PCa is Radical Prostatectomy (RP), which is the surgical approach for the complete removal of the prostate, and among its side effects is Urinary Incontinence (UI). This dysfunction occurs mainly due to the removal of part of the urethral sphincter as a consequence of the procedure. The objective of this work was to analyze by means of a bibliographic review the efficiency of Physical Therapy in patients with Urinary Incontinence after Radical Prostatectomy. The method used was bibliographic research in national and international articles in databases such as Pubmed, Scielo, BIREME and LILACS. 67 works were found, from which 9 were selected. The selected articles presented evaluation of the effect of physical therapy treatment in patients with UI after RP. It was possible to find evidence of UI reduction regardless of the technique used. However, even with evidence of acquisition of continence after RP, a standardization of methods and protocols used was not found. Therefore, it is suggested that more studies be conducted in the area.